A new species of Agnaptoria Reitter (Coleoptera: Tenebrionidae: Blaptini) from Dhaulagiri Zone in Nepal. (2nd July 2020) - Li, Yun-Chun; Shi, Ai-Min
ABSTRACT: A new species of darkling beetle (Tenebrionidae) belonging to the genus Agnaptoria Reitter, 1887, A. jinchengi sp. nov . is described from the Dhaulagiri Zone in Nepal. A new key for all known Agnaptoria species is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:64D8CC42-A7DB-4CCA-B52B-C54E2F1C114F